Load-aware user association algorithm based on potential game theory for UDN with CoMP - Jia YU; Yachao LIANG; Shushi GU; Ye WANG (物联网学报)
A load-aware user association (LAUA) algorithm based on potential game theory for ultra dense network (UDN) with coordinated multi-point (CoMP) transmission technique was proposed.LAUA algorithm was capable to balance the load of base stations on the premise of satisfying users’ demand for quality of service,avoid over loading problem in heterogeneous UDN.This algorithm was applicable to the Internet of things application scenario that required uploading vedio data and other data transmission rates.The effectiveness of the proposed algorithm was proved by the simulation experiment.